Influence of Educational Campaigns on Community Knowledge About Chronic Kidney Disease: Results from a Community-Based Campaign - Mothana Al Jabr; Nouf Alalmaei; Jory Almulhim; Sadeem Saad Alkaluf; Nour Ali Alnhwi; Abdulrahman Alrashed; Khalid Alkhawfi; Doaa Alabdulkraim; Saleh Alyousef; Mohammed Yousef Al Mulhim; Muthana Abdullah Al Sahlawi; Ossama Zakaria (International Journal of Environmental Research and Public Health, 2026)
Chronic kidney disease (CKD) is an emerging public health problem, and low public awareness may result in late diagnosis and poor outcomes. We evaluated baseline knowledge of CKD among participants in a community awareness campaign and immediate knowledge change following a focused educational intervention. The study was designed as a biphasic pre- and post-intervention study that took place over the course of a 3-day public campaign that coincided with World Kidney Day on 13 March 2025. The campaign consisted of six educational stations on important topics of CKD, blood-pressure and blood-glucose measurements, with access to nephrologist consultation. Participants completed a validated questionnaire prior to and after attending the campaign. The changes in knowledge about kidney function, risk factors, symptoms, diagnostic methods, and treatment were evaluated. A total of 134 responses were received; 102 participants were eligible and completed both assessments. Knowledge scores and several item-level response proportions were higher immediately after campaign participation than before participation. The knowledge of diabetes mellitus as a risk factor for CKD increased from 34.3 to 80.4%, the knowledge of blood tests for renal assessment increased from 52.0 to 80.4%, and the knowledge of pharmacological treatments that slow down the progression of CKD increased from 52.9 to 78.4%. The percentage of people who think that herbal medicines are effective to treat CKD decreased from 19.6% to 8.8%. No demographic or clinical predictors of change in overall knowledge were statistically significant, although differences were seen in specific knowledge domains. These findings show higher CKD knowledge immediately after participation in a structured community campaign. Controlled studies with longer follow-up are needed to determine causality, durability, behavior change, and clinical impact.